2017
DOI: 10.1136/jclinpath-2017-204367
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600 mutation detection in melanoma: a comparison of two laboratory testing methods

Abstract: The rate of BRAF mutation in our cohort (28.8%) was lower than international published rates of 40%-60%. This may reflect ethnic or geographic differences within population cohorts. The high concordance rate of PCR and immunohistochemical methods in determining BRAF status suggests that immunohistochemistry is potentially a viable, cost-effective alternative to PCR testing and suitable as a screening test for the BRAF mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Cases were regarded as positive if there was any evidence of cytoplasmic BRAF staining (1+, 2+, or 3+; see Figure ). This interpretation was used by our group previously in the validation of BRAF IHC …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases were regarded as positive if there was any evidence of cytoplasmic BRAF staining (1+, 2+, or 3+; see Figure ). This interpretation was used by our group previously in the validation of BRAF IHC …”
Section: Methodsmentioning
confidence: 99%
“…More recently, the development of a monoclonal antibody specific for BRAF V600E has made it feasible to test for mutant BRAF protein by immunohistochemistry (IHC). Multiple studies have demonstrated high concordance between results of testing by RT‐PCR and IHC . RT‐PCR is more widely validated and may identify rare mutations (such as V600K) that are not detectable on IHC but predict response to BRAF inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In malignant melanoma, the BRAF‐V600E mutation is associated with tumor aggressiveness and poor prognosis . The assessment of BRAF gene status is part of standard practice in patients diagnosed with metastatic melanoma and it is currently detected by DNA‐based methods, such as polymerase chain reaction (PCR) . However, the utilization of IHC to detect the VE1 antibody is rapidly emerging as a trustworthy technique to determine BRAF mutation status in patient tissue samples .…”
Section: Applications Of Predictive Biomarkersmentioning
confidence: 99%
“…However, the utilization of IHC to detect the VE1 antibody is rapidly emerging as a trustworthy technique to determine BRAF mutation status in patient tissue samples . Studies have shown high concordance rates among PCR and IHC methods in determining BRAF status, which suggests that immunohistochemistry is a viable and cost‐effective alternative to PCR testing that may be suitable as a screening test for the BRAF mutation in melanoma . The BRAF V600E mutation accounts for close to 50% of all BRAF mutations in NSCLC and has been associated with micropapillary histologic features.…”
Section: Applications Of Predictive Biomarkersmentioning
confidence: 99%